La participación ciudadana en el contexto de desarrollo sustentable (Civil participation in sustainable development context) - Guillén, A.; Badii Zabeh, Mohammad Hosein; Blanco Jiménez, Mónica; Sáenz López, Karla Annett Cynthia (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. Progress of the society is mainly based upon three areas: economic, social and environmental. This progress is ought to be conducted in a conscientious and respectable manner including the policies pertained to.